Orientación al mercado y su efecto en la satisfacción en las relaciones comerciales entre fabricantes y distribuidores de productos farmacéuticos en Jalisco, México (Market orientation and its effect in the satisfaction with respect to the commercial relations between manufacturing & distribution of pharmaceutical products, Jalisco, México) - González, E. R. (Facultad de Contaduría Pública y Administración U.A.N.L., 2006)
Abstract. The market orientation is a process through as information is generated on the markets of the company; such information by all the organization is scattered and who sustains the decision making; and finally, the organizational answer of the company based on own actions of a direction towards the client and the surroundings. The market orientation has been studied from two main perspectives, the cultural perspective and the perspective of behaviors. The cultural market orientation sustains in the values and beliefs on the decision making in the market leading to actions on strategies to the market that are originated from within. The other perspective, the one of behaviors, are based on a set of actions those that not necessarily have a cultural base, although some raise that all oriented behavior to the market is consequence of a system of beliefs that sustains them. However, several scales have been developed to measure the market orientation from a perspective or another one. It has been verified that both scales from the market orientation are convergent as far as the measurement of such phenomenon. A measurement becomes of the perception from market orientation through the perspective of behaviors and of the economic and psychological satisfaction experienced by both parts in the relation (in a sample of 54 wholesale distributors and 14 manufacturers), being that the perception from direction to the market influences more of important way in the economic satisfaction, no in the psychological satisfaction. In the work a valuation becomes of these results. Resumen. La orientación del mercado es un proceso a través del cual se genera información de los mercados de la empresa. Tal información se dispersa por toda la organización; y finalmente, se diseña la respuesta organizativa de la empresa a través de las acciones dirigidas hacia el cliente y el entorno. La orientación del mercado se ha estudiado a partir de dos perspectivas, la cultural y la de comportamientos. La orientación cultural del mercado se sostiene en los valores y creencias que permiten la toma de decisiones de estrategias al mercado originadas desde dentro de la empresa. La otra perspectiva, la de comportamientos, se basa en un sistema de acciones los que no necesariamente tienen una base cultural, aunque todo comportamiento orientado al mercado es consecuencia de un sistema de creencias que los sostiene. Sin embargo, varias escalas se han desarrollado para medir la orientación del mercado de una perspectiva u otra. Se ha verificado que ambas escalas de la orientación del mercado son convergentes para medir el fenómeno. En este trabajo se utiliza una de la orientación del mercado bajo la perspectiva de comportamientos y se relaciona con la satisfacción económica y psicológica experimentada por ambas partes en la relación (en una muestra de 54 distribuidores al por mayor y de 14 fabricantes). Con ello se obtiene que la orientación al mercado influencia de manera más importante la satisfacción económica, y no en la satisfacción psicológica. En el trabajo se evidencian estos resultados.